Mannitol metabolism during pathogenic fungal–host interactions under stressed conditions - Upadhyay, Ram S.; Meena, Mukesh; Prasad, Vishal; Zehra, Andleeb; Gupta, Vijai K. (Frontiers in Microbiology, 2015)
Numerous plants and fungi produce mannitol, which may serve as an osmolyte or metabolic store; furthermore, mannitol also acts as a powerful quencher of reactive oxygen species (ROS). Some phytopathogenic fungi use mannitol to stifle ROS-mediated plant resistance. Mannitol is essential in pathogenesis to balance cell reinforcements produced by both plants and animals. Mannitol likewise serves as a source of reducing power, managing coenzymes and controlling cytoplasmic pH by going about as a sink or hotspot for protons. The metabolic pathways for mannitol biosynthesis and catabolism have been characterized in filamentous fungi by direct diminishment of fructose-6-phosphate into mannitol-1-phosphate including a mannitol-1-phosphate phosphatase catalyst. In plants mannitol is integrated from mannose-6-phosphate to mannitol-1-phosphate, which then dephosphorylates to mannitol. The enzyme mannitol dehydrogenase plays a key role in host-pathogen interactions and must be co-localized with pathogen-secreted mannitol to resist the infection.